Increasing target engagement via customized electrode positioning for personalized transcranial electrical stimulation: A biophysical modeling study - Rodgers, Griffin; Joodaki, Mahyar; Hopf, Alois; Santarnecchi, Emiliano; Guzman, Raphael; Müller, Bert; Osmani, Bekim (NeuroImage (Orlando, Fla.), 2025)
•Digital design and 3D printing of TES caps could allow for flexible positioning of stimulation electrodes.•We provide an in silico proof-of-concept that more flexible positioning significantly increases target engagement.•Personalized optimization with >64 available electrode positions outperformed other montages in terms of correlation of the electric field magnitude with the target and focality across all achievable target intensities.•Further gains are expected if design constraints are better integrated into the montage selection approach. Transcranial electric stimulation (TES) is a non-invasive neuromodulation technique with therapeutic potential for diverse neurological disorders including Alzheimer's disease. Conventional TES montages with stimulation electrodes in standardized positions suffer from highly varying electric fields across subjects due to variable anatomy. Biophysical modelling using individual's brain imaging has thus become popular for montage planning but may be limited by fixed scalp electrode locations. Here, we explore the potential benefits of flexible electrode positioning with 3D-printed neurostimulator caps. We modeled 10 healthy subjects and simulated montages targeting the left angular gyrus, which is relevant for restoring memory functions impaired by Alzheimer's disease. Using quantitative metrics and visual inspection, we benchmark montages with flexible electrode placement against well-established montage selection approaches. Personalized montages optimized with flexible electrode positioning provided tunable intensity and control over the focality-intensity trade-off, outperforming conventional montages across the range of achievable target intensities. Compared to montages optimized on a reference model, personalized optimization significantly reduced variance of the stimulation intensity in the target. Finally, increasing available electrode positions from 32 to around 86 significantly increased target engagement across a range of target intensities and current limits. In summary, we provide an in silico proof-of-concept that digitally designed and 3D-printed TES caps with flexible electrode positioning can increase target engagement with precise and tunable control of applied dose to a cortical target. This is of interest for stimulation of brain networks such as the default mode network with spatially proximate correlated and anti-correlated cortical nodes. [Display omitted]